Side-group chemical gating via reversible optical and electric control in a single molecule transistor - Linan Meng (Nature Portfolio, 2019)
It remains a challenge to fully control molecular electronics. Here, Meng et al. show a reversible two-mode single-molecule switch, where the conductance through the molecular backbone is controlled by an in situ chemical gating via bias-dependent trans–cis isomerisation on an azobenzene sidegroup.